The role of extra-membranous inter-helical loops in helix-helix interactions. - Ulmschneider, M; Tieleman, D; Sansom, MS (2005)
The effect of a short loop connecting two transmembrane alpha-helices was studied using molecular dynamics simulations. Helices F and G from bacteriorhodopsin and two corresponding polyalanine helices were embedded in octane and POPC membranes in a transmembrane configuration both with and without the inter-helical loop. The results indicate that the membrane environment and the sequence of the loop are more influential on the dynamics and structure of the motif than the presence of a loop as such, at least for the time-scales investigated. The four residues in the FG loop are stabilized by four hydrogen bonds. These hydrogen bonds are not present in the polyalanine loop, causing it to be more flexible than the FG loop. This effect was observed independently of the protein environment, stressing the importance of the sequence. The structural analysis indicates that the loop has weak stabilizing properties in all environments. The stabilization due to the presence of the loop was strongest in a simulation of the FG fragment in a membrane-mimetic octane slab. In the simulations of the helix-loop-helix motif embedded in an explicit lipid bilayer model, the lipid bilayer interface compensates to a large extent for the absence of the loop.